Exploring novice designers acceptance of the use of a tool for modeling the interaction and usability of information systems - Marques, Anna; Fonseca, Clara; Saraiva, Larissa; Coelho, Natália; Finotti, Caio; Sousa, Francisco Wilkinis (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Usability is considered one of the most important quality factors determining the success/failure of the actual use of an interactive information system. Early usability aims to support thinking about, designing, and evaluating usability issues in the early phases of development. Solution: The tool USINN Modeler was developed to support the interaction and usability modeling of interactive information systems based on the notation USINN. Problem: In the technological transfer process of the tool, it is important to guarantee that the companies that adopt it will remain competitive and add value to their products/services. Method: A laboratory evaluation with novice designers was conducted to investigate their acceptance of the tool. IS Theory: The tool was evaluated using the instrument proposed by the Technology Acceptance Model 3 (TAM3). Results: The results indicated a high level of usefulness perceived by novice designers and the need to review the tool’s usability. Contributions: This study provides valuable insights into the usability and adoption of the USINN Modeler tool, offering contributions to interactive information systems design.